Physical, Chemical, and Sensory Characteristics of Star Fruit (Averrhoa carambola L.) Jelly Candy with Various Concentrations of Carrageenan-Konjac and Carrageenan-Pectin - Bara Yudhistira; Siti Rahma Hamidah; Fuangfah Punthi (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2024)
Star fruit, a widely consumed fruit in Indonesia, is utilized in jelly sweets as a functional food promoting health. Nevertheless, the exorbitant price of gelatin, a gelling agent compatible with halal requirements, has resulted in the substitution of carrageenan, a comparable substance with a fragile consistency. This study investigated the physical, chemical, and sensory properties of star fruit jelly candy using different concentrations of gelling agents. This study employed a fully randomized design to investigate the effects of various concentrations and types of gelling agents, namely carrageenan-konjac and carrageenan-pectin, at concentrations of 1.5%, 2.0%, and 2.5%, respectively. The findings indicate that various gelling agents impact the characteristics of hardness, gumminess, chewiness, water content, antioxidants, and pH. Different amounts of gelling agents impact the firmness, stickiness, texture, separation of liquid, moisture level, mineral content, acidity, moisture availability, and crude fiber content. The variations in outcomes of this study are determined by the hydrocolloid’s water content, which can bind water. Subsequently, the duration of processing and the level of temperature exert an influence on these parameters, hence impacting the physical qualities. The findings indicate that the combination of carrageenan and konjac substantially affects star fruit jelly candy’s physical and chemical characteristics. The optimal formula for creating star fruit jelly candy is to employ a 2.5% concentration of carrageenan-konjac.